HUBUNGAN ANTARA LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PANEN KELAPA SAWIT DI PT GUNTA SAMBA ESTATE PENGADAN - Dinda Chantika Maulani; Sri Ngapiyatun; Silvi Dwi Mentari (Politeknik Pertanian Negeri Samarinda, 2020)
The physical occupational environment influences garden productivity and employee performance, where the better the environment, the more the productivity increases. A satisfying work environment for its employees can increase productivity and work performance. In contrast, inadequate work environments will be able to lower productivity and work performance and can eventually lower employee motivation. A working environment is said to be good or appropriate when humans can optimally carry out activities, wholesome, safe, and comfortable. The workplace harmony is seen in the long term. A poor working environment can require more labor and more time and do not support an efficient system design. The study aims to analyze the correlation between the employees' physical work environment to the performance of harvest workers in the samba estate of. Whether or not there is a correlation between the environment of employees' physical labor to the performance of employees in the samba estate of, the research is focused on the longevity of the plants, topography and safety of the harvest workers in afdeling 1 in pt gunta samba development estate. The research target is employees who work for the harvest. As for the research object is the work performance of palm harvesting employees.. It is hoped that the results will provide sufficient information to ensure that there is no link between the employees' physical work environment and the performance of employees at the age of gunta samba estate. Data collection techniques use questionnaires that have been tested as validity and religious tests. The data analysis technique used is Pearson and product product correlation analysis. Based on the results of the study using Pearson correlation and product presents the value of 0,000 which is smaller than 0.05 (0,000 < 0.05), which means variable x (employee physical working environment) has significant connections with variable y (employee performance).